Implementation of CSR PT. Wika Beton, Tbk-Ppb Sumut in the Field of Education Through the “Wika Teaching” Program in SMK Negeri 2 Binjai - Idolla Adha Yanti; Badaruddin Badaruddin; Indra Fauzan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Social Responsibility or what we are better known as CSR today is an inseparable aspect of the company. Providing CSR assistance in the field of education with the "Wika Teaching" program by PT Wika Beton Tbk, can increase wider knowledge and also learn about the world of work which can help improve welfare. The purpose of this study was to analyze the implementation of CSR PT. Wika Beton, Tbk-PPB North Sumatra in the field of education through the "Wika Mengajar" program at Smk Negeri 2 Binjai. Analyzing and the constraints faced in the implementation of CSR PT. Wika Beton, Tbk-PPB North Sumatra in the field of education through the "Wika Mengajar" program at Smk Negeri 2 Binjai. This type of research is descriptive qualitative research. The method used to collect data in this study is observation, interviews and documentation, in this research the data is analyzed by means of data reduction, data display, and Drawing conclusions and verification. The results of the research on the Implementation of the Wika Teaching Program at SMK Negeri 2 Binjai from several indicators taken according to the implementation theory of the Merilee S Grindle Model from the aspect of policy content, namely the influencing interests, the benefits generated, the degree of desired change, the location of decision making, program implementation and resources. which is used while in the aspect of the policy environment, namely the power, interests and strategies of the actors involved, as well as the characteristics of the institutions and regimes in power and the level of compliance and the response from the implementers.The target of the Wika Mengajar program is to fulfill corporate responsibility through the implementation of CSR by creating the Wika Mengajar program and to provide assistance to its steak owners through the program company PT. Wika Concrete.